Peran CSR Pertamina Fuel Terminal Tasikmalaya melalui program BALENAGARA (Budidaya Lele Sukanagara) - Ridha Nuralia Fauziah; Ardi Hutri Prayitno (Universitas Muhammadiyah Sumatera Utara, 2022)
This paper aims to analyze the corporate social responsibility (CSR) program carried out by PT Fuel Terminal Tasikmalaya. The implementation of the community empowerment program as a CSR activity of the company encourages the improvement of the community's economy. No longer carrying out charity programs, the company is now implementing CSR programs by implementing empowerment programs (community empowerment). Through the BALENAGARA (Cultivation Catfish Sukanagara) program, the company assists the group to develop into an independent and sustainable group. In order to achieve independence, the company implements a program implementation strategy starting from planning, implementation, monitoring to evaluation. The data in this paper uses sources from literature reviews, company documents and sources. This paper encourages to understand the CSR practices and strategies carried out by PT Pertamina Fuel Terminal Tasikmalaya in the implementation of the BALENAGARA program (Cultivation of Catfish Sukanagara) not only in the implementation of responsibility but aiming at sustainability and community independence.Keywords: CSR, Empowerment, Economy, Community